THE IMPLEMENTATION OF CONTENT-BASED APPROACH IN IMPROVING ACADEMIC WRITING SKILLS OF EFL STUDENTS - Heriyawati, Dwi Fita; Sulistyo, Teguh; Sholeh, Agus (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
This study aimed at investigating the benefits of the implementation of Content-Based Approach (CBA) in academic writing of EFL settings. Therefore, the approach was implemented in writing class in which 35 students participated as the respondents of the study. They were treated with CBA and their essays were then analyzed to examine the effects of the implementation of the approach on their writing products. Besides, this study investigated further the grammatical errors made by the students as reflected on their essays. The findings of this study proved that CBA is beneficial to improve students’ writing skills even though the students still produced grammatical errors.